Optical properties of nanostructured carbon and gold nanoparticle hybrids. Issue 1700 (2014) - Li, Yuan; Chopra, Nitin
ABSTRACT: We report simulation of optical properties of hybrid geometry comprised of multilayer graphene shell encapsulated gold nanoparticles loaded with carbon nanotubes. The discrete dipole approximation (DDA) method was employed. The results indicated that the optical properties of encapsulated gold nanoparticles were not suppressed by the carbon material coating. Furthermore, low scattering effects were also observed. The simulation method helped visualize the near-surface normalized electric field, which is directly related to the intensity of hot spots on the surface of these hybrid nanoarchitectures.